Dynamic risk stratification using serial measurements of plasma concentrations of natriuretic peptides in patients with heart failure. (15th October 2018) - Zhang, J.; Pellicori, P.; Pan, D.; Dierckx, R.; Clark, A.L.; Cleland, J.G.F.
Abstract: Background: Prognostic models for patients with chronic heart failure are generally based on a single assessment but treatment is often given with the intention of changing risk; re- evaluation of risk is an important aspect of care. The prognostic value of serial measurements of natriuretic peptides for the assessment of changes in risk is uncertain. Aims: To evaluate the prognostic value of serial measurements of plasma amino-terminal pro-brain natriuretic peptide (NT-proBNP) during follow-up of out-patients with chronic heart failure (CHF). Methods: Patients diagnosed with CHF between 2001 and 2014 at a single out-patient clinic serving a local community were included in this analysis. NT-proBNP was measured at the initial visit and serially during follow-up. Only patients who had one or more measurements of NT-proBNP after baseline, at 4, 12 and/or 24 months were included. Results: At baseline, amongst 1998 patients enrolled, the median age was 73 (IQR: 64–79) years, 70% were men, 31% were in NYHA class III/IV, and 77% had NT-proBNP >400 pg/mL. Median follow-up was 4.8 (IQR: 2.5–8.6) years. Serial measurements of NT-proBNP improved prediction of all-cause mortality at 3 years (c- statistic = 0.71) compared with using baseline data only (c-statistic = 0.67; p < 0.001) but a model using only the most recent NT-proBNP had an even higher c-statistic (0.72; p < 0.001). Similar results were obtained based on long-term prediction of mortality using all available follow-up data. Conclusions: Serial measurement of NT-proBNP in patients with CHF improves prediction of all-cause mortality. However, using the most recent value of NT-proBNP has similar predictive power as using serial measurements. Highlights: In patients with CHF most prognostic information is carried by the most recent value of NT-proBNP. Plasma NT-proBNP changes little over time despite intensification of disease-modifying therapies for heart failure. Further similar analyses are required in other populations to validate our findings.